2011
DOI: 10.1109/tnet.2011.2112376
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Communities in Sparse MANETs

Abstract: In sparse mobile ad hoc networks, placement of services and data is crucial to assure their availability to all nodes because sparse population of nodes can lead to (frequent) network partitions. If these dynamic networks display a fairly stable cluster structure, it is possible to utilize this structure to improve service and data availability. However, clustering in a dynamic network is a very challenging task due to the ever-changing topology and irregular density of such a network. In this paper, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…To solve this problem, a layer aggregation approach (De Domenico et al 2014) is proposed to reduce data size or as a data filter to benefit network-analysis outcomes. Since Mucha et al (2010) introduced the multiplex modularity optimization method, numerous attempts were made in this field (Drugan et al 2011;Nguyen et al 2011;Li and Garcia-Luna-Aceves 2013), which opened up a upsurge in unveiling the communities in time-varying networks. Taylor et al (2017) proposed the random matrix theory and found layer aggregation to significantly influence detectability.…”
Section: Temporal Network Partitionmentioning
confidence: 99%
“…To solve this problem, a layer aggregation approach (De Domenico et al 2014) is proposed to reduce data size or as a data filter to benefit network-analysis outcomes. Since Mucha et al (2010) introduced the multiplex modularity optimization method, numerous attempts were made in this field (Drugan et al 2011;Nguyen et al 2011;Li and Garcia-Luna-Aceves 2013), which opened up a upsurge in unveiling the communities in time-varying networks. Taylor et al (2017) proposed the random matrix theory and found layer aggregation to significantly influence detectability.…”
Section: Temporal Network Partitionmentioning
confidence: 99%
“…SSM is one of the most commonly used mobility models for simulating real-life mobile applications [212], [213]. This mobility model has been an attractive target for MANETs, and many scholars have employed it to conduct their experiments [214]- [216]. The Long Term Evolution (LTE) is one the use cases for this mobility model, which has gained lots of attention as it is being the defacto technology for 4G infrastructures [217]- [219].…”
Section: Figure 37: Movements Of Nodes In Ssmmentioning
confidence: 99%
“…Drugan et. al [25] modify the modularity-based approach of Newman and Grivan [18], the random walk approach proposed by van Dongen [26] and the q-spin Potts model proposed by Reichard and Bornholdt [27], to accept as input the topology table maintained by the OLSR routing protocol [6] rather than a complete graph. The paper demonstrated that the OLSR topology table was sufficient to accurately detect the communities in the network without additional overhead, under the given network conditions.…”
Section: Community Detection Applications and Related Workmentioning
confidence: 99%